Logistics operations management in the Industry 4.0 era: a case study for transition of an automotive company′s operations to fourth-party logistics structure - Döner, Hülya; Vayvay, Özalp; Vardarlier, Pelin; Kalender, Zeynep Tuğçe (Transport, 2025)
In recent years, the understanding of minimum inventory and customer satisfaction in the flow of goods and services from manufacturers to end-users is of great importance among the factors that make businesses more interested in outsourcing logistics activities. Additionally, technological transformation and customer requests for complicated technology and services caused the appearance of new circumstances, which is progressively altering the industry. In this regard, choosing, managing and coordinating between multiple vendors become very difficult and time consuming so, companies outsource more functions while supply chain operations getting more complex. Companies generally preferred 3PL providers for their logistics functions including packaging design and management of company-owned assets. On the other hand, with technological transformation in logistic sector, businesses are looking to outsource 4PL more than ever. 4PL system transitions are difficult processes since it requires comprehensive system integration and should be well understood by the company′s supply chain team. Today, although the importance of 4PL systems is more understood and this structure is becoming more widespread, many companies still face similar adaptation problems. From this point of view, it is believed that this study creates important insights into the business world. In this study, the transition process of an automotive company is examined which successfully completed after a 5-month project period. As a detailed case study, the Transportation Management Module (TTM) is selected since the whole transition process was very comprehensive and included many dimensions. Study revealed that adaptation of the new system, developed by the partnership of the automotive company and 4PL company, provided several benefits. In this sense, with the transition of Transportation Management (TM), TTM is reduced by 2 days, almost 10% savings are reported in the whole company and only in the Turkey branch, 243311 € cost saving is achieved in the 1st year. The study proves that focusing on the core business via outsourcing supply chain activities not only increases efficiency in the selected automotive company but also increases supply chain quality as well.First published online 22 January 2026